2018
DOI: 10.1128/jvi.02251-17
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin Facilitates Enterovirus 71 Infection by Mediating Viral Entry

Abstract: Fibronectin (FN) is a high-molecular-weight extracellular matrix protein that contains the RGDS motif, which is required to bind to integrins. Synthetic RGDS peptides have been reported to compete with FN to bind to the cell surface and inhibit the function of FN. Here, we identified that synthetic RGDS peptides significantly inhibit human enterovirus 71 (EV71) infection in cell cultures. In addition, mice treated with RGDS peptides and infected with EV71 had a significantly higher survival rate and a lower vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 52 publications
3
26
0
Order By: Relevance
“…Most of these alternative attachment receptors cannot initiate uncoating. The involvement of attachment receptors is demonstrated during infection of cultured cells, and most were reported in only a single publication [39][40][41][43][44][45]. Therefore, neither the mode of internalization nor the uncoating activity has been confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these alternative attachment receptors cannot initiate uncoating. The involvement of attachment receptors is demonstrated during infection of cultured cells, and most were reported in only a single publication [39][40][41][43][44][45]. Therefore, neither the mode of internalization nor the uncoating activity has been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin is a high molecular weight glycoprotein that plays important roles in cell adhesion, growth, migration, and differentiation [124]. He et al [44] found that overexpression of fibronectin enhanced EV-A71 infection, and that knockout of fibronectin reduced viral binding to host cells and decreased viral yield. A short peptide containing an Arg-Gly-Asp (RGD) motif, which is known to inhibit interaction between integrin and fibronectin, inhibited EV-A71 infection in cultured cells and in neonatal mice.…”
Section: Fibronectinmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, miRNAs were found to play important roles in the viral replication of EV71. In the present study, we found that upregulation of miR-545 was induced by EV71 infection in HEK293 and RD cells, where these two lines have been commonly used as an in vitro cell model for EV71 infection(He et al, 2018;B. Wang, Zhang, & Zhao, 2013;Yue et al, 2017).…”
mentioning
confidence: 55%
“…SCARB2 binds EVA71 on the southern rim of the canyon (Zhou et al, 2019) and expelles the pocket factor from the EVA71 virion, hence destabilizing the capsid and triggering the uncoating process (Dang et al, 2014). In addition, other host factors on the cell surface are reported to facilitate EVA71 entry, such as Annexin A2, fibronectin, vimentin and nucleolin (Du et al, 2014;He et al, 2018;Su et al, 2015;Yang et al, 2011). These receptors were identified as binding receptors to capture EVA71 on the cell surface.…”
Section: Introductionmentioning
confidence: 99%